Convergent and stereoselective synthesis of trisubstituted E-alkenyl bromides and iodides via beta-oxido phosphonium ylides. - Hodgson, D; Arif, T (2008)
β-Oxido phosphonium ylides, generated in situ from aldehydes and Wittig reagents [alkylidene(triphenyl)phosphoranes, other than ethylidene(triphenyl)phosphorane], react readily with electrophilic halogen sources to form predominantly or exclusively E-bromo- or iodosubstituted alkenes. The stereochemical outcome on halogenation is remarkably sensitive to alkylidene size [ethylidene(triphenyl)phosphorane is highly Z-selective]. Copyright © 2008 American Chemical Society.